INTERNATIONAL LAW INSTRUMENT ON MIGRANT WORKERS - Putu Pramayuni Karisma Devi; kadek Dedy suryana; AA Sagung Poetri Paraniti (Universitas Mahendradatta, 2022)
Certain international law regulations have been set to provide protection for migrant workers. Three Specific International Instruments committed to migrant workers namely ILO Convention No. 97 concerning Migration for Employment (Revised) 1949,1 ILO Convention No. 143 on Migrant Workers (Supplementary Provisions) 19752 and The United Nation International Convention on the protection of the Rights of all Migrant Workers and their Families 1990 (ICRMW).3 Though the intention to bring forth international standard of safe guard has been specifically incorporated into various United Nation and International Labor Organization convention, migrant workers are still vulnerable to labour exploitation. According to the survey in the 2012, the ILO estimated that 20.9 million people are in forced labour globally, trafficked for labour and sexual exploitation or held in slavery-like conditions.4 This essay is trying to examine how state has notable influence not only in preventing but also creating precarious condition of migrant workers